The Prognosis and Risk Stratification Based on Pelvic Lymph Node Characteristics in Patients With Locally Advanced Cervical Squamous Cell Carcinoma Treated With Concurrent Chemoradiotherapy. Issue 8 (October 2016) - Li, Xin; Wei, Li-Chun; Zhang, Ying; Zhao, Li-Na; Li, Wei-Wei; Ping, Li-Jian; Dang, Yun-Zhi; Hu, Jing; Shi, Mei
Abstract : Background: The purpose of this study is to determine the prognostic significance of pelvic lymph node (PLN) characteristics and perform risk stratification in patients undergoing concurrent chemoradiotherapy for locally advanced cervical squamous cell carcinoma. Methods: We retrospectively reviewed the records of 609 patients with Federation Internationale de Gynecologie et d'Obstetrique (FIGO) stage II to IVa who underwent concurrent chemoradiotherapy, compared overall survival (OS), distant metastasis-free survival (DMFS), and pelvic recurrence-free survival between patients with or without PLN involvement. We further analyzed prognostic factors for OS and DMFS including FIGO stage, tumor volume, and lymph node (LN) characteristics in 300 patients with PLN involvement. Results: The 3-year OS rate was 81.7% versus 92.8% ( P = 0.002) and the 3-year DMFS rate was 79.3% versus 92.7% ( P = 0.006) in patients with or without PLN involvement, respectively. With univariable analysis, FIGO stage, LN-volume, LN-number, LN-diameter, and matted/necrotic LN affected both OS and DMFS. Based on multivariable analysis, we created a risk stratification model. For OS, the independent risk factors were FIGO stage III or IVa, LN-volume of 3 cm 3 or more, LN-diameter of 1.5 cm or more, and matted/necrotic LN. The low-risk group (no risk factors), mid-risk group (1 or 2 risk factors), and high-risk group (3 or 4 risk factors) had a 3-year OS of 96.6%, 84.9%, and 64.7%, respectively ( P = 0.005). For DMFS, LN-diameter of 1.5 cm or more, LN-number of 3 or more, and matted/necrotic LN were the independent risk factors. The subgroups for DMFS were the low-risk group (no risk factors), the mid-risk group (1 risk factor), and the high-risk group (2 or 3 risk factors), and the 3-year DMFS was 92.4%, 76.2%, and 64.6%, respectively ( P = 0.001). Conclusions: The prognosis was significantly poorer for patients with high-risk lymph node characteristics. Using this risk stratification, we should select the most appropriate and individualized treatment modality to improve outcomes in those patients with a poorer prognosis.